Doing 'reciprocity work': The role of fieldworkers in a mass drug administration trial in the Gambia. Issue 12 (2nd December 2022) - Fehr, Alexandra; Nieto-Sanchez, Claudia; Muela, Joan; Manneh, Ebrima; Baldeh, Dullo; Ceesay, Omar; D'Alessandro, Umberto; Dabira, Edgard; Kingori, Patricia; Peeters Grietens, Koen; Bardají, Azucena; Bunders-Aelen, Joske; et al.
ABSTRACT: In their roles as nurses, data collectors, or other, fieldworkers undertake myriad tasks working intimately with and on the bodies of others – a type of work called 'body work'. This work further includes the micro-political relations shaping these interactions, and studies have shown the importance of these relationships in the success of clinical trials, particularly in the Gambia. This study seeks to expand the concept of body work to understand the roles and interactions of fieldworkers within the trial community, and the effect on a mass drug administration (MDA) clinical trial. We conducted a mixed-methods social science study alongside the MDA in 2018–2019, including in-depth interviews, focus group discussions, and semi-structured observations with the population involved (and not) in the MDA, as well as the MRC fieldworkers. We found that fieldworkers participated in what we call 'reciprocity work'. Through their regular tasks and interactions, they necessarily showed respect and established trust in a way that formed and contributed to reciprocal relationships, the results of which impacted the trial and individuals' autonomy in the decision-making process. Understanding the role of fieldworkers and their reciprocity work is a vital component in comprehending how research ethics are made and conducted in global health research.